The Terminology of Thuma’ninah in the Qur’an: Al Qurtubi’s Interpretation and Mental Health Relevance - Nur ‘Alim Muhammad Kautsar; Jihan Kharisma Hidayatulloh; Ainur Rhain (al-Afkar, Journal For Islamic Studies, 2026)
The rising cases of stress, anxiety, and mental health disorders highlight the growing need for inner tranquillity. The Qur’an introduces the concept of al-thuma’ninah, yet its meanings across different verses have not been comprehensively examined through the lens of classical exegesis. Previous studies largely focus on semantic or contemporary approaches, leaving a gap in understanding how classical scholars conceptualised thuma’ninah. This study addresses this gap by analysing the meaning of al-thuma’ninah according to al-Qurtubi’s Tafsir al-Jami‘ li Ahkam al-Qur’an, using qualitative library research and thematic analysis of Qur’anic verses derived from the root ط-م-أ-ن. The research aims to identify the categories of thuma’ninah and explore their relevance to mental health. The findings show that al-thuma’ninah is a multidimensional concept encompassing epistemological reassurance, psychospiritual calm, steadfast faith under pressure, social stability, and illusory worldly tranquillity. These results affirm its relevance as a spiritual foundation for modern mental well-being.